1973
DOI: 10.1029/rg011i004p00855
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the magnetic viscosity of lunar and terrestrial rocks

Abstract: Lunar materials exhibit two distinct types of viscous or time-dependent magnetic behavior. Igneous rocks and largely recrystallized breccias, whose magnetic properties are due to multidomain iron, typically have weak magnetic viscosity, but decay persists for very long times following even a brief exposure to a field. Lunar soils and low metamorphic grade breccias, which contain an impor[ant fraction of metallic iron of singledomain and superparamagnetic size, generally acqtlire an anomalously strong viscous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 33 publications
(20 reference statements)
4
68
0
1
Order By: Relevance
“…However, the amount of viscous remanence for each sample, that decays in 10 4 sec., is always about 30% lower than the VRM acquired for the same time period. This observation is consistent with the considerations of Dunlop (1973) and Worm et al (1988), where it is shown that for an assembly of SD particles after equally long acquisition and decay times, 37% of the acquired magnetization still survives during VRM decay in zero field. However, this is not observed for sample K1 from the recent soil So, where VRM decay removes almost all of the VRM acquired.…”
Section: Discussionsupporting
confidence: 79%
“…However, the amount of viscous remanence for each sample, that decays in 10 4 sec., is always about 30% lower than the VRM acquired for the same time period. This observation is consistent with the considerations of Dunlop (1973) and Worm et al (1988), where it is shown that for an assembly of SD particles after equally long acquisition and decay times, 37% of the acquired magnetization still survives during VRM decay in zero field. However, this is not observed for sample K1 from the recent soil So, where VRM decay removes almost all of the VRM acquired.…”
Section: Discussionsupporting
confidence: 79%
“…First, the log t relationship is critically dependent on the nature of the grain distribution f(v,Hco) for non-interacting SD grains, where v is the volume and Hco the microscopic coercive force (Dunlop, 1973). Consequently, if a sample contains discontinuities in f(v,H ), the slope S may change co with time.…”
Section: Acquisition Of Viscous Remanent Magnetizationmentioning
confidence: 99%
“…The possibility that the stable magnetization is a viscous remanent magnetization (VRM) acquired during the current polarity epoch, is highly unlikely because most single domain grains have very much longer relaxation times. Mild heating (~200°C) will erase readily such a VRM (Dunlop, 1973), yet no significant change in magnetization was recognized during thermal demagnetization. Because magnetite is, except under very special conditions, of detrital origin, the stable magnetization was acquired during or soon after deposition.…”
Section: Magnetic Mineralogymentioning
confidence: 99%